ANALISIS PERGESERAN MAKNA TATO SUKU DAYAK IBAN PADA GENERASI MUDA DI DESA BATU LINTANG - Sepa, Novita Wana; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out about, "Shifting the Meaning of Iban Dayak Tribal Tattoo Culture in Young Generation". The research method used is descriptive method with a form of qualitative research. Data sources of this research are primary data sources and secondary data sources. Data collection techniques used were observation, interview and documentation techniques, while the data collection tools used were observation guides, interview guides and documentation. The analysis in this study was presented in a descriptive qualitative manner using 4 informants consisting of the oldest people in Batu Lintang Village 2 people and 2 young people. The shift in meaning of Iban tattoos to the younger generation really does occur among the younger generation because, it has been seen when generations make tattoos by adding new motifs or tattoo strokes and when making tattoos Iban young generation also no longer need to migrate or labor in the forest. Sehingga dimasa sekarang ini tato Iban sudah tidak memiliki arti bagi masyarakat Dayak Iban.Keywords: Teaching Method, Lectures, Question and Answer